Ministry of Social Development Sarawak / Widya Hana Nurulhuda Mohd Salihin - Mohd Salihin, Widya Hana Nurulhuda (Universiti Teknologi MARA, Sarawak, 2015)
Ministry of Social Development embodied in the state cabinet reshuffle in 1985 with the merger of the two ministries, the Ministry of Youth Culture and Sports, the Ministry of Welfare. The ministry subsequently changed its name to the Ministry of Social Development and Urbanisation in 2000. In 2011, this Ministry was again renamed as the Ministry of Social Development. The organization is located at 3rd Floor, Masja Building, 93502, Petra Jaya, Kuching, Sarawak. This building also has other governmental organizations such as Ministry of Agriculture Modernisation, Ministry of Land Development, Ministry of Local Government and Community Development, Ministry of Tourism, Ministry of Infrastructure Development and Communications and Ministry of Welfare, Women and Family Development.